A NEW STAGE OF COOPERATION BETWEEN UZBEKISTAN AND TURKEY - Komilova Nigorabonu Ravshanjon qizi (Web of Journals Publishing, 2024)
Cooperation between Uzbekistan and Turkey has developed sharply in recent years and reached a new strategic level. Relations between the two countries are deepening due to Uzbekistan's new policy of reforms and Turkey's interest in strengthening strategic partnership in the region. This cooperation covers the political, economic, cultural and security spheres and strengthens the influence of Central Asia and Turkey in the international arena.
Keywords: Uzbekistan, Turkey, Central Asia,